Explanatory factors of premature marriages of adolescent girls: Study conducted in the Diulu Health Zone, Mbujimayi City, DRC - NGIELE, Constantine; Kitengie, L. B.; Botomba, S. N.; Ngbolua, K. N.; Balow’a, I. K.; Omanyondo, M. O. (Orapuh Journal, 2025)
Introduction Adolescent marriage is a significant public health problem worldwide, particularly in the Democratic Republic of the Congo (DRC), due to its high prevalence (38%) and its consequences on the lives of young mothers who are unfamiliar with the requirements of sexual and reproductive health. Purpose This study aimed to understand the explanatory factors and complications of teenage marriages in the Diulu Health Zone in Mbujimayi City, Democratic Republic of the Congo. Methods It is a cross-sectional analytical study, using semi-structured interviews, direct structured interviews, and direct observation, with a sample size of 398 adolescent girls. Results The results show that many adolescent girls (41.5%) are married at a mean age of 13.95 ± 2.35 years. This difference in the average age of respondents is statistically significant (p < 0.05), with a p-value of 0.000. Married girls have a lower average age than unmarried girls. The educational level of many is primary school (40.5%). The factors that significantly influenced the marriage of the teenage girls surveyed included their parents’ lack of financial means (82.4%), abuse in the place of accommodation (p < 0.05; OR = 0.28; p = 0.000), religion (p < 0.05; OR = 1.53; p = 0.042), and parental death (p < 0.05; OR = 0.571; p = 0.003). These factors, dominated by parental poverty, parental death, low level of education, environmental influence, and customs, contribute to adolescent marriage. Divorce, maternal-fetal death, and school drop-out are the most frequent complications. Conclusion Adolescent marriage is a common practice in Africa in general, and in the Democratic Republic of the Congo in particular. This study found that the dominant factors explaining adolescent marriages are poverty, parental death, limited access to formal education, large family size, and social influence. Multi-sectoral, multidisciplinary awareness-raising and the education of young girls are crucial assets that can help reduce teenage marriages and prepare them for a brighter future. To reduce the prevalence of teenage marriage, effective multi-sectoral and multidisciplinary awareness efforts are needed.